Pengaruh Umur Potong dan Konsentrasi Larutan Asam Asetat terhadap Sifat Fisik dan Kimia Gelatin Kulit Babi - Sompie, M.; Triatmojo, S.; Pertiwiningrum, A.; Pranoto, Y. (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
This research was aimed to study the influence of animal age and acetic acid solution concentration on physical and chemical properties. The experiment used Randomized Complete Design (RCD) with two factors and three replicates. The first factor was animal age consisted 3 levels (5, 7 and 9 months). The second factor was concentration of acetic acid solution consisted of 3 levels (2, 4 and 6 percents). The result showed that interaction of animal age period and concentration of acetic acid had no significant effect on gel strength, moisture content, ash content and fat content of pig skin gelatin. It was concluded that pigskin gelatin from ages of 5, 7 and 9 months and concentration acetic acid 2, 4 and 6 % had similar physical and chemical peoperties with the commercial gelatin.